Impact of tumor size on survival outcome of pancreatic carcinoma following pancreatic resection: A systematic review and meta-analysis - Shrestha, Anuj; Baskota, Attit; Li, Fu Yu; Ma, Wen-Jie; Yang, Qin; Jie, Hu-Hai; Bijukchhe, Sunil Man (Asian Journal of Medical Sciences, 2018)
The aim of the study was to evaluate the influence of tumor size on long-term survival outcome of pancreatic tumors following pancreatic resection and the possibility of implementing another tumor size cut-off point in AJCC pancreatic tumor staging. Literature searches was conducted on electronic database to identify relevant studies on tumor size related survival outcome following pancreatic resection for pancreatic adenocarcinoma. Meta-analysis was done using the effect estimates and the use of 95% confidence intervals (CIs) was done to calculate the pooled risk estimates; heterogeneity among studies was examined using I2 statistic. Total of 18 trials (13 retrospective and 5 prospective studies) including 6230 elderly patients was included in this study. The pooled HR of the tumor size with 2 cm cut-off was 1.43 with 95% CI of [1.27-1.62], I2= 17%, p<0.00001 and was statistically significant. Median survival for tumor size <2, >2, <3, >3, <4 and >4 were 41.02 months, 16.20 months, 19.41 months, 10.79 months, 24.2 months and 15.14 months respectively and the 1-, 3-, and 5-year survival rate decreased with increasing tumor diameter. Importantly, a total of four studies results indicated that 3-year survival rate and a total of five studies results indicated that 5-year survival rate had statistical significance with 3 cm cut-off. Tumor diameter of 2 cm seems to be a reasonable but relatively less comprehensive cut-off point. 3 cm cut-off maybe become a new potential tumor size cut-off point in addition to the current sole 2 cm cut-off point defining tumor stage. Asian Journal of Medical Sciences Vol.9(1) 2018 1-10